Learning, changing and doing : Critical citizenship through ecumenical exposure - Nell, Ian (Stellenbosch Theological Journal, 2016)
Critical citizenship is becoming a very significant part of the educational pedagogy at Stellenbosch University relating to the vocational, personal and civic lives of the students and lecturers, focusing on critical and reflective thinking in what to learn, believe and do. Making use of the central concepts of critical citizenship as hermeneutical lenses, the main research question of this article is: "Does the exposure through ecumenical tours, as part of the programme in the Postgraduate Diploma in Theology in Christian Ministry, foster critical citizenship, and if so, in what ways?" The purpose of the article is therefore to take a closer look at one component of this specific programme and to see if, and in what ways, critical citizenship is embedded and fostered through aspects of ecumenical exposure. Factors at play in ecumenical exposure include the diversity of the student population, the content of the programme and, especially, the participatory and reflective practices of living faith communities. A pedagogical framework will be used to evaluate whether critical citizenship is enhanced through the ecumenical exposure of the programme.